Compressive creep of SiC whisker/Ti3SiC2 composites at high temperature in air. Issue 10 (6th July 2020) - Dash, Apurv; Malzbender, Jürgen; Dash, Khushbu; Rasinski, Marcin; Vaßen, Robert; Guillon, Olivier; Gonzalez‐Julian, Jesus
Abstract: The compressive creep of a SiC whisker (SiCw ) reinforced Ti3 SiC2 MAX phase‐based ceramic matrix composites (CMCs) was studied in the temperature range 1100‐1300°C in air for a stress range 20‐120 MPa. Ti3 SiC2 containing 0, 10, and 20 vol% of SiCw was sintered by spark plasma sintering (SPS) for subsequent creep tests. The creep rate of Ti3 SiC2 decreased by around two orders of magnitude with every additional 10 vol% of SiCw . The main creep mechanisms of monolithic Ti3 SiC2 and the 10% CMCs appeared to be the same, whereas for the 20% material, a different mechanism is indicated by changes in stress exponents. The creep rates of 20% composites tend to converge to that of 10% at higher stress. Viscoplastic and viscoelastic creep is believed to be the deformation mechanism for the CMCs, whereas monolithic Ti3 SiC2 might have undergone only dislocation‐based deformation. The rate controlling creep is believed to be dislocation based for all the materials which is also supported by similar activation energies in the range 650‐700 kJ/mol. Abstract : The creep resistance of Ti3 SiC2 increases with increasing volume of SiCw . The compsite with 20 vol% SiCw shows a higher stress exponent as compared to the material with 0 and 10 vol% SiCw . Stacking faults are visible in composite with 10 vol% of SiCw . The dislocations are pinned at the SiCw ‐Ti3 SiC2 interface in the case of the composite with 20 vol% of SiCw .